Prevalence of eustrongylides ignotus in poecilia reticulata obtained from some wastewater drains of Lagos state (2012)
Poecilia reticulata is a common ornamental tropical fish‘is fouhd in many wastewater drains in Nigeria. Guppies feed on Oligochaetes which are intermediate hosts of Eustrongylides ignotus which is a parasite of Clarias gariepinus. The potential ban on the importation of ornamental fishes into Nigeria due to dearth of information on the parasite fauna of ornamental fishes .has enhanced the demand for local species, usually sourced from the wild. Sampling was done monthly using a 2 mm mesh-sized scoop net along selected drains at Igi-Olugbin Street, Basil Ogamba Street,, Ahmadu Bello Road and Adenaike Alagbe Street between March, 2004 and February, 2005. The selected drains were abutting residences and varying industrial activities in each of four different local government areas of Lagos State. 60 female and 60 male samples were randomly selected from each drain for dissection and microscopy. Nematodes observed were identified using standard identification guides. Prevalence was determined as percentage infection in guppies examined. Measurements of wastewater temperature, Dissolved Oxygen (DO), pH and transparency were done according to APHA methods: Drain depth was determined using a calibrated pole. Data was analyzed using chi-square test, ANOVA and Pearson correlation coefficient. Out of 4,320 n samples examined only 156 were infected. There was no sex-related difference in the prevalence of E. ignotus and no significant difference in mean monthly pH and DO across drains. The highest prevalence of 12.0% was observed in P. reticulata males obtained from Adenaike Alagbe . Street in June, 2004. Mean monthly physicochemical parameters for drains were: temperature, 25.0 ± 1.1- 26.0 ± 1.1 0 C; DO, 7.8 ± 2.1 - 8.4 ± 1.8 mg 1; pH, 6.9 ± 0.5 - 7.3 ± 0.4; transparency, 3.5 ± 0.8 - 23.0 ± 3.6 cm and drain depth, 9.6 ± 2.3 - 14.8 ± 3.2 cm. The prevalence of E. ignotus in the P. reticulata obtained from the selected Streets should not prevent their exploitation for both import substitution and the export market because it is low